Terapi Meditasi Zikir untuk Mengurangi Kecemasan Menghadapi Persalinan - Rachmawati Ika Sukarsih (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Pregnant women experience changes in their bodies, both physically and psychologically. Pregnant women experience worry, anxiety, and fear during pregnancy, when facing labor, and after delivery, especially in primigravidas. Meditation is one of the complementary efforts in overcoming anxiety in pregnant women. Meditation concentrates the mind to help women think positively and provide a sense of calm and happiness. This study aimed to determine the effect of meditation therapy on reducing anxiety in facing childbirth.Methods: This research is quantitative; the research design is quasi-experimental with the One Group Pretest Posttest Design. The population in this study were all mothers giving birth at RSI Darus Syifa' Surabaya in May - June 2018, with a total of 42 people. Furthermore, purposive sampling was carried out to obtain a sample of 30 respondents. This study's therapy of dhikr meditation is a form of worship using dhikr once for 12 minutes by reciting Tasbih, Tahlil, Tahmid, Takbir, and Basmalah. The research instrument was the Anxiety Scale for Pregnant (ASP) to determine anxiety scores. Data analysis used paired t-test statistics.Results: Respondents who experienced decreased anxiety scores were 28 people, respondents with fixed anxiety scores were two people, and no respondents experienced increased anxiety scores. Based on the results of the hypothesis testing, the sig value (-2 tailed) = 0.000, so 0.000 <0.05. This shows a significant effect before and after dhikr meditation on decreasing the average anxiety score.Conclusion: There was a significant effect before and after the dhikr meditation therapy was carried out on reducing maternal anxiety in facing childbirth. The results of this study are expected to be used by midwives in providing midwifery care to pregnant women who experience anxiety before delivery as a form of non-pharmacological treatment.